2019
DOI: 10.3390/su11102752
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Homogenization or Heterogenization? The Effects of Globalization on Carbon Dioxide Emissions, 1970–2014

Abstract: Globalization significantly influences climate change. Ecological modernization theory and world polity theory suggest that globalization reduces carbon dioxide emissions worldwide by facilitating economic, political, social, and cultural homogenization, whereas ecological unequal exchange theory indicates that cumulative economic and political disparities lead to an uneven distribution of emissions in developed and less developed countries. This study addresses this controversy and systematically investigates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 119 publications
(143 reference statements)
0
4
0
Order By: Relevance
“…In addition, it delivers services with reduced investment costs by applying procedures and regulations that foster economic development and thus help to reduce carbon emissions. This finding is contradict with that of Wang et al (2019) and align with those of Acheampong (2019).…”
Section: Effects Of Financial Development On Carbon Emissions In Africacontrasting
confidence: 71%
“…In addition, it delivers services with reduced investment costs by applying procedures and regulations that foster economic development and thus help to reduce carbon emissions. This finding is contradict with that of Wang et al (2019) and align with those of Acheampong (2019).…”
Section: Effects Of Financial Development On Carbon Emissions In Africacontrasting
confidence: 71%
“…Low-carbon development and environmental protection requires reducing CO 2 emissions, on the one hand, and taking into account the social and economic development, on the other hand. Wang et al analyzed the internal tension between environmental conservation and degradation in a globalizing world and discussed the opportunities for less developed countries to reduce emissions [11]. Luo et al quantified direct and indirect emissions associated with off-site construction, and the results indicated that conducting a well-articulated assessment was important to assist with decision making on environmental impact reduction [12].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mandatory government environmental laws and regulations and competitive pressures have a significant positive effect on enterprise green practices, while enterprise green practices have a significant positive effect on environmental performance [32]. A study that analyzed data from 1970 to 2014 for 137 countries found that international political integration helped reduce carbon emissions, and discussed opportunities for less developed countries to reduce their emissions [33]. In a study based on panel data of 108 cities in the Yangtze River Economic Zone from 2003-2017, technological innovation was evidenced to have a significant positive effect in promoting green development, showing a U-shaped nonlinear relationship, and this relationship varied by region [34].…”
Section: Ecological Modernization Theorymentioning
confidence: 99%